Nanotoxicology and nanotechnology interplay towards a safe and responsible innovation - Silva, Maria João (2018)
The European Union Strategic and Action Plan for Nanosciences and Nanotechnologies emphasizes the need of ensuring the development of safe, integrated, and responsible nanotechnologies and nanotechnology products. Indeed, although the use of manufactured nanomaterials (NM) is widespread and has been considered greatly beneficial for several scientific and technological areas, uncertainties about their safety still remain, representing a challenge to scientists, risk assessors and regulators. Recent studies of the team have been aimed at assessing the potential deleterious effects, e.g., genotoxicity that is intimately associated with carcinogenicity, of several classes of NM, using complementary in vitro and in vivo approaches, nested within the conventional risk assessment paradigm. Overall, the results have suggested that specific physicochemical properties of NM are crucial to define their nano-bio interactions and their toxic potential. Furthermore, our findings reinforced previous reports suggesting that factors inherent to experimental conditions and methodologies may affect the effects observed. These and other nano-specific issues have been hindering the categorization of NM according to their toxicity and, consequently, their risk assessment and management. Nonetheless, considering the wide array of NM produced or under development, a case-by-case approach to the risks of each NM seems an unreasonably extensive task. Thus, the development of high-throughput omics-based tools adapted for the toxicity assessment of NM and, on the other hand, the elucidation of the cellular and molecular mechanisms underlying NM toxicity is of utmost importance to progress faster in the field of nanotoxicology. Such information will allow the development of cost-efficient screening strategies and promote predictive nanotoxicology, driving the synthesis of safer NM. The ultimate goal is fostering a sustainable and safe innovation in the field of nanotechnologies.